Understanding practices of UK college governing: Rethinking strategy and accountability - Steve Garner (Educational Management Administration & Leadership, 2023)
College governing boards are widely held to be the keystone of institutional strategy and the prime locus of support, challenge and accountability in respect of the actions of the senior Executive. Whilst there are many normative prescriptions about the conditions and arrangements required for effective college governance, relatively little is known about how and to what extent the practices of boards reflect or realise these prescriptions. This paper draws upon a unique research study of eight further education colleges across the four nations of the UK. Following Chia and MacKay and Hendry et al., our ‘strategy as practice’ approach gives primacy to emergence and immanence through board practices. Video and observational data, supplemented by some interview and documentary data are used to develop an understanding of governing practices. Our analysis suggests that current normative prescriptions lack the conceptual sophistication required to support governing as it really happens. We offer a reconceptualisation of both strategy and accountability suggesting that the latter includes lateral, inward- and outward-facing functions that make conflicting demands on governors. We argue that these distinctions are vital in enabling further positive development of governing in the college sector.